A Creative Thinking Process of Junior High School Students in Solving Story Problems Viewed from Field Dependent – Field Independent Cognitive Style - Halliem Pangesti Ningrum; Endah Budi Rahaju (MATHEdunesa, 2023)
Giving math subjects is very important in life. This is in line with content standards in Permendiknas No. 22 of 2006 that mathematics subjects need to be given to train and teach thinking skills, one of which is creative thinking. The purpose of this study was to describe the creative thinking processes of junior high school students with field dependent and field independent cognitive styles in solving problems on the material surface area of geometric figures. The subjects in this study were one student each with field dependent and field independent cognitive styles who had high and equal mathematical abilities and were male. The research instruments used were GEFT sheets to classify cognitive styles, Mathematical Ability Test (MAT) sheets to classify students' mathematical abilities, Problem Solving Task sheets (PST) and interview guidelines to find out in detail the students' creative thinking processes. Based on the results of the research conducted, the creative thinking process of students with field dependent cognitive style at the preparatory stage read the questions twice to understand the questions, at the incubation stage field dependent students needed 15 minutes to get out of this stage. At the illumination stage, field dependent students were not fluent in solving problems and only had one solution idea. At the verification stage, field dependent students are unsure of their answers and have no other solution ideas. The thinking process of students with field independent cognitive styles in the preparation stage of field independent students read the questions twice to understand the questions. At the incubation stage, independent field students managed to get out of this stage and found ideas to solve questions for 5-10 minutes. In the illumination stage, field independent students smoothly solve problems and have several ideas for solving them. At the verification stage, field independent students are very confident with their answers and have other solutions.